The Effect of Raw Material Quality and Production Process on Product Quality On Chips Business in Pringsewu Regency - Agus Purnomo; Hanif Permana Tsany (Cita konsultindo, 2024)
This journal aims to investigate the effect of raw material quality as well as the production process on product quality in the chip business in Pringsewu Regency. Product quality has a very important role in determining the competitiveness and success of a business, especially in the chip industry, which is one of the leading commodities in the region. The research method used in this journal is a case study by collecting data through direct interviews with chip producers, direct observation of the production process, and analysis of product samples produced. The collected data were then analyzed using descriptive statistical methods and regression analysis to measure the relationship between the variables of raw material quality, production process, and product quality. The results showed a significant influence between the quality of raw materials as well as the production process for product quality in the chip business in Pringsewu Regency. Good raw material quality, which includes cleanliness, purity, and consistency, as well as the implementation of good and efficient production processes, positively affect the quality of the final product.